Renin–angiotensin system inhibitors positively impact on multiple aging regulatory pathways: Could they be used to protect against human aging? - Cavanagh, Elena M. V.; Inserra, Felipe; Ferder, León (Physiological reports, 2024)
The renin–angiotensin system (RAS)—a classical blood pressure regulator—largely contributes to healthy organ development and function. Besides, RAS activation promotes age‐related changes and age‐associated diseases, which are attenuated/abolished by RAS‐blockade in several mammalian species. RAS‐blockers also increase rodent lifespan. In previous work, we discussed how RAS‐blockade downregulates mTOR and growth hormone/IGF‐1 signaling, and stimulates AMPK activity (together with klotho, sirtuin, and vitamin D‐receptor upregulation), and proposed that at least some of RAS‐blockade's aging benefits are mediated through regulation of these intermediaries and their signaling to mitochondria. Here, we included RAS‐blockade's impact on other aging regulatory pathways, that is, TGF‐ß, NF‐kB, PI3K, MAPK, PKC, Notch, and Wnt, all of which affect mitochondria. No direct evidence is available on RAS/RAS‐blockade‐aging regulatory pathway–mitochondria interactions. However, existing results allow to conjecture that RAS‐blockers neutralize mitochondrial dysfunction by acting on the discussed pathways. The reviewed evidence led us to propose that the foundation is laid for conducting clinical trials aimed at testing whether angiotensin‐converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB)—even at subclinical doses—offer the possibility to live longer and in better health. As ACEi and ARB are low cost and well‐tolerated anti‐hypertension therapies in use for over 35 years, investigating their administration to attenuate/prevent aging effects seems simple to implement. Aging is accompanied with changes in (i) signaling pathways that regulate the aging process, that is, TOR, AMPK, insulin/IGF‐1, TGF‐beta, NF‐kB, PI3K, MAPK, PKC, Notch and Wnt; (ii) activity and responsiveness of the renin–angiotensin system (RAS); (iii) epigenetic modulation of gene expression. These changes negatively impact on mitochondrial function, resulting in tissue damage and loss of function. RAS contributes to aging by promoting (i–iii). ACEi/ARB (RAS‐blockers)—even at subclinical levels—can block/attenuate (i–iii) thereby reducing age‐related decline. Well‐designed clinical trials would clarify whether long‐term low‐level RAS‐blockade can prolong human life and reduce age‐associated disease. ROS, reactive oxygen species; MDP, mitochondria‐derived peptides.